Morphological and functional features prognostic factor of magnetic resonance imaging in locally advanced rectal cancer. (July 2019) - Fusco, Roberta; Granata, Vincenza; Rega, Daniela; Russo, Carolina; Pace, Ugo; Pecori, Biagio; Tatangelo, Fabiana; Botti, Gerardo; Izzo, Francesco; Cascella, Marco; Avallone, Antonio; Delrio, Paolo; et al.
Background: Although imaging can be suggestive of the diagnosis of rectal cancer, the primary imaging role is to assist in treatment triage of histologically diagnosed tumors. The possibility of a multimodal approach in the response to the treatment opens the way for the selection of criteria more personalized to the patient. Purpose: To assess the prognostic factor of morphological and functional magnetic resonance imaging (MRI) in rectal cancer. Material and Methods: Seventy-seven patients were enrolled and underwent MRI before treatment and 59 patients underwent MRI after treatment. Radiologists evaluated the presence of lesions using a 4-point confidence scale; they recorded anatomical side, extent, and distance from the anorectal junction and distance from the circumferential margin. Tumor location was classified according to the involvement of proximal rectal channel and/or distal rectal channel. Radiologists scored signal intensity on T2-weighted (T2W) images, diffusion-weighted images (DWI), and MRI dynamic enhancement pattern. Tumor regression grade (TRG) and pathological T (pT) were the gold standard. Results: Lesion vascularization score before treatment showed a predictive value of complete pathological response (sensitivity 88%, specificity 50%) based on pT, while using TRG lymph node number before treatment (sensitivity 83%, specificity 57%) showed a predictive value for response treatment. T2W signal (sensitivity 78%, specificity 30%) and DWI signal after treatment (sensitivity 78%, specificity 61%) showed a good predictive value for local rectal recurrences. Conclusions: Lesion vascularization and lymph node number had a predictive value for neoadjuvant treatment complete response in rectal cancer. T2W signal intensity and DWI signal showed a good predictive value for local rectal recurrences.